2020
DOI: 10.1101/2020.05.27.20114843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ACE2 polymorphisms as potential players in COVID-19 outcome

Abstract: The clinical condition COVID-19, caused by SARS-CoV-2, was declared a pandemic by the WHO in March 2020. Currently, there are more than 5 million cases worldwide, and the pandemic has increased exponentially in many countries, with different incidences and death rates among regions/ethnicities and, intriguingly, between sexes. In addition to the many factors that can influence these discrepancies, we suggest a biological aspect, the genetic variation at the viral S protein receptor in human cells, ACE2 (angiot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…Albeit, the study was limited to 45 patients, which is insufficient to establish significant conclusions. While another recent study highlighted the impact of the activating variant N720D (rs41303171) on epidemiological disparities, especially in Europeans when compared to other global populations [ 59 ] and stands in support of our observations.…”
Section: Discussionsupporting
confidence: 90%
“…Albeit, the study was limited to 45 patients, which is insufficient to establish significant conclusions. While another recent study highlighted the impact of the activating variant N720D (rs41303171) on epidemiological disparities, especially in Europeans when compared to other global populations [ 59 ] and stands in support of our observations.…”
Section: Discussionsupporting
confidence: 90%
“…A twins study estimated that total heritability of Covid-19 risk was 50% (95% CI 29-70%) [13]. Analyses of host genomes indicate that ACE2 and OR4C5 gene variants may impact severity of Covid-19 [14,15]. OR4C5 is a pseudogene in the olfactory receptor loci region that codes for a G-protein-coupled receptor arising from a single-coding exon gene.…”
Section: Introductionmentioning
confidence: 99%
“…Further research using the 100 000 genomes project has suggested that ACE2 polymorphisms could explain the higher risk of severe disease and death amongst males and those of African and East Asian origin in SARS-CoV-2 infection. The Chinese SARS-CoV-2 study could reflect the literature which suggests subjects with ‘severe disease’ may represent a sub-group with ACE2 polymorphisms 6 . It is already known that rs182366225 and rs2097723 polymorphisms are more frequent in the East Asian population and increase the expression of ACE2.…”
Section: Discussionmentioning
confidence: 87%